2020
DOI: 10.1002/cb.1829
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the predictive validity of perceived globalness and country of origin of foreign brands in quality judgments among consumers in emerging markets

Abstract: Consumers in emerging markets are known to have strong preferences for well‐known foreign brands. Drawing on schema and categorization theories, this study empirically investigates how accessible two components of brand foreignness – globalness and country of brand origin – are in consumer perceptions of brand quality in emerging markets. In addition, we argue that brand globalness can be shaped by inferential reasoning and test how consumer perceptions of brand globalness are affected by both a brand's countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Country of origin studies inquires into consumer attitudes toward a product or a brand due to the originating country. In those studies, the 'country of origin effect' is accepted to shape consumer attitudes (C. M. Han, 2020;Herz & Diamantopoulos, 2017;Janda & Rao, 1997;Suh, Hur, & Davies, 2016;C. K. Wang & Lamb, 1983; Y.…”
Section: Perceived Brand Foreignness and Perceived Brand Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Country of origin studies inquires into consumer attitudes toward a product or a brand due to the originating country. In those studies, the 'country of origin effect' is accepted to shape consumer attitudes (C. M. Han, 2020;Herz & Diamantopoulos, 2017;Janda & Rao, 1997;Suh, Hur, & Davies, 2016;C. K. Wang & Lamb, 1983; Y.…”
Section: Perceived Brand Foreignness and Perceived Brand Qualitymentioning
confidence: 99%
“…Foreignness is not limited to a specific country, as consumer perception is related to a brand's more general characteristics and can be explained through perceived brand foreignness. Whether a brand is foreign or domestic is a more general categorical division in the mind of consumers than that of the origin country-oriented division (Batra et al, 2000;Samiee, Shimp and Sharma, 2005;Zhou, Yang,, and Hui, 2010), which is narrow in terms of being restricted to merely one country (Askegaard & Ger, 1998;C. M. Han, 2020).…”
Section: Perceived Brand Foreignness and Perceived Brand Qualitymentioning
confidence: 99%
“…Categorization theory posits in consumer research that “consumers construct and use categorical representations to classify, interpret, and understand the information they receive” ( Loken et al, 2008 ). The term “category” refers to the information kept in the memory and is later utilized to classify and assign products or services to a consumer category ( Han, 2020 ). In the process of brand categorization, consumers develop brand prototypes according to their perceptions, and these prototypes assist them in product evaluation ( Loken, 2005 ).…”
Section: Theoretical Context and Hypotheses Developmentmentioning
confidence: 99%
“…This line of research has demonstrated that COO influences product evaluation and purchase intention (Suh et al , 2016; Alshibly et al , 2019; Souiden et al , 2020), attitudes toward brand acquisitions (Nguyen and Alcantara, 2020), brand love (Cho and Hwang, 2020), brand equity (Cowan and Guzman, 2020), perceived product authenticity (Cheah et al , 2018; Melewar and Skinner, 2020) and destination evaluations (Zhang et al , 2016). Prior research shows that consumers are more influenced by COO than by brand globalness (Han, 2020). If COO information about a certain product is not available, consumers will search online for it (Cheah et al , 2018).…”
Section: Literature and Theoretical Frameworkmentioning
confidence: 99%